Utilization of Artificial Intelligence Features in The Canva Application for the Development of Islamic Teaching Modules for Teachers - Yuliana Ervina Andriani; Saryanto Saryanto (STAI Serdang Lubuk Pakam, 2025)
This study aims to explore the use of artificial intelligence features in the Canva application for the development of Islamic Teaching Modules by teachers at SDN Muntilan. In the digital age, the use of technology in education is increasingly important to improve the quality of learning. This study uses a qualitative approach with a case study method, involving 10 teachers who actively use Canva. Data were collected through observation, in-depth interviews, and documentation, then analyzed thematically. The results showed that the artificial intelligence features in Canva made it easier for teachers to design teaching modules, increased time efficiency, and encouraged creativity in the creation of teaching materials. However, several technical challenges, such as dependence on a stable internet connection and limited access to devices, were obstacles. The implication of this study is that the use of Canva can be an effective tool to improve the quality of Islamic Teaching Modules, provided that there is technical support to overcome existing obstacles. This study contributes to the development of educational technology, particularly in teaching at the elementary school level.